Enhancing treatment efficiency of swine wastewater by effluent recirculation in vertical-flow constructed wetland - He, Lian-sheng; Liu, Hong-liang; Xi, Bei-dou; Zhu, Ying-bo (Journal of environmental sciences (China), 2006)
Livestock wastewater has been a major contributor to Chinese cultural eutrophication of surface waters. Constructed wetlands are under study as a best management practice to treat wastewater from dairy and swine operations, but the removal efficiency of pollutants is relatively low. Enhancing the treatment efficiency of livestock wastewater by effluent recirculation was investigated in a pilot-scale vertical-flow constructed wetland. The wetland system was composed of downflow and upflow stages, on which narrow-leaf Phragmites communis and common reed Phragraites Typhia are planted, respectively; each stage has a dimension of 4 m^2 （2 m × 2 m）. Wastewater from facultative pond was fed into the system intermittently at a flow rate of 0.4 m^3/d. Recirculation rates of 0, 25%, 50%, 100% and 150% were adopted to evaluate the effect of the recirculation rate on pollutants removal. It shows that with effluent recirculation the average removal efficiencies of NH4-N, biological oxygen demand （BOD5） and suspended solids（SS） obviously increase to 61.7%, 81.3%, and 77.1%, respectively, in comparison with the values of 35.6%, 50.2%, and 49.3% without effluent recirculation. But the improvement of TP removal is slight, only from 42.3% to 48.9%. The variations of NH4-N, dissolved oxygen（DO） and oxidation-reduction potential（ORP） of inflow and outflow reveal that the adoption of effluent recirculation is benefi- cial to the formation of oxide environment in wetland. The exponential relationships with excellent correlation coefficients （R2 〉0.93） are found between the removal rates of NH4-N and BOD5 and the recirculation rates. With recirculation the pH value of the outflow decreases as the alkalinity is consumed by gradually enhanced nitrification process. When recirculation rate is kept constant 100%, the ambient temperature appears to affect NH4-N removal, but does not have significant influence on BOD5 removal.